2003
DOI: 10.1080/02688690310001611242
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of intracranial hypertension in encephalic cryptococcosis

Abstract: The incidence of cryptococcosis has risen sharply together with the growing number of patients with Acquired Immunodeficiency Syndrome (AIDS). Cryptococcal meningitis is nowadays the most common intracranial non-viral infection in such cases. One of its most serious complications is intracranial hypertension (ICH), a situation that can lead either to early death, or disabling sequelae. The authors analyse a series of 10 cases of encephalic cryptococcosis with ICH, and describe the clinical course, diagnosis, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 6 publications
1
42
0
4
Order By: Relevance
“…Once the patients have VPS conditions, VPS should be performed because VPS therapeutic effects are certain. It was reported that 21 patients recovered after VPS (100%) [4][5][6][7], which is consistent with our results (91.6%) (11 patients all recovered except one patient who wanted to discharge).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Once the patients have VPS conditions, VPS should be performed because VPS therapeutic effects are certain. It was reported that 21 patients recovered after VPS (100%) [4][5][6][7], which is consistent with our results (91.6%) (11 patients all recovered except one patient who wanted to discharge).…”
Section: Discussionsupporting
confidence: 95%
“…So far, only 21 patients with CM have received VPS [4][5][6][7], demonstrating that surgeons do not exactly know the therapeutic effects and indication of VPS for CM. In the past, we also had the same confusion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the cryptococcal meningitis series by Calvo et al, 5 there was a 40% rate of ventriculitis in patients with external ventricular drains. Lumbar and ventricular drains are generally placed at the bedside and do not achieve the same standards of antisepsis required by intraoperative placement of shunts.…”
Section: Role Of Lumbar and Ventricular Drainsmentioning
confidence: 99%
“…It is well known that the formation of cerebro-spinal fluid takes place in the choriod plexuses in ventricles, and in man its total volume is about 140 ml with total daily production about 500 ml or 0.25% of total volume per minute [341] . The arachnoid projections begin to develop at or around the time of birth and occur in abundance only in the adult [342,345,346] . The functional importance of brain fluid drainage is apparent whereas the mechanisms responsible for it still remain unclear.…”
Section: Role Of Lymphatic Vessels In Brain Fl Uid Exchangementioning
confidence: 99%